Structural analysis of an agroforestry area in a portion of the xeric shrubland of northeast of Mexico - Alanis Rodriguez, Eduardo; Valdecantos Dema, Alejandro; Canizales Velázquez, Pamela Anabel; Collantes Chavez-Acosta, Alejandro; Rubio Camacho, Ernesto; Mora Olivo, Arturo (Instituto de Ecología, A.C., 2018)
Background and Aims: The studies of plant communities allow to know the impacts caused by the agricultural and livestock activities, especially in arid zones. The objective of this work was to contrast the diversity, composition and structure of the arboreal and shrub strata of three areas (Agroforestry, Regenerated and Reference) of the xerophilous scrub.Methods: In each area four sampling sites of 1600 m2 each one were established randomly, where all arboreal and shrubby individuals were registered and censused. In each area, ecological parameters were calculated, as well as the Shannon and Margalef indices.Key results: In the three areas, a total of 25 species of vascular plants belonging to 22 genera and 15 families were registered. The best represented family was Fabaceae with nine species, being the genus Acacia the one that presented the largest species number (three). The observed values of species richness, the Shannon index, Margalef index and abundance between the Reference and Agroforestry area were similar, and both were significantly higher than the values of the Regenerated area. The Agroforestry area presented lower abundance but greater dominance compared with the other two areas studied, and it was the area that reached the highest percentage of similarity with the Reference area.Conclusions: The Agroforestry activity contributes in a certain way in the maintenance of the diversity and composition of vascular plants of the Tamaulipan thorn scrub studied; and this activity does not allow to change to a large extent the composition and structure of this type of vegetation.